Right Ventricular Long Noncoding RNA Expression in Human Heart Failure. (March 2015) - Di Salvo, Thomas G.; Guo, Yan; Su, Yan Ru; Clark, Travis; Brittain, Evan; Absi, Tarek; Maltais, Simon; Hemnes, Anna
The expression of long noncoding RNAs (lncRNAs) in human heart failure (HF) has not been widely studied. Using RNA sequencing (RNA-Seq), we compared lncRNA expression in 22 explanted human HF hearts with lncRNA expression in 5 unused donor human hearts. We used Cufflinks to identify isoforms and DESeq to identify differentially expressed genes. We identified the noncoding RNAs by cross-reference to Ensembl release 73 (Genome Reference Consortium human genome build 37) and explored possible functional roles using a variety of online tools. In HF hearts, RNA-Seq identified 84, 793 total messenger RNA coding and noncoding different transcripts, including 13, 019 protein-coding genes, 2, 085 total lncRNA genes, and 1, 064 pseudogenes. By Ensembl noncoding RNA categories, there were 48 lncRNAs, 27 pseudogenes, and 30 antisense RNAs for a total of 105 differentially expressed lncRNAs in HF hearts. Compared with donor hearts, HF hearts exhibited differential expression of 7.7% of protein-coding genes, 3.7% of lncRNAs (including pseudogenes), and 2.5% of pseudogenes. There were not consistent correlations between antisense lncRNAs and parent genes and between pseudogenes and parent genes, implying differential regulation of expression. Exploratory in silico functional analyses using online tools suggested a variety of possible lncRNA regulatory roles. By providing a comprehensive profile of right ventricular polyadenylated messenger RNA transcriptome in HF, RNA-Seq provides an inventory of differentially expressed lncRNAs, including antisense transcripts and pseudogenes, for future mechanistic study.